The 2014-15 Bárðarbunga-Holuhraun magmatic rifting episode: A seismic study - Agustsdottir, Thorbjorg (Hughes Hall, 2018)
On 16 August 2014 an unusual sequence of earthquakes began near the southeastern rim of the ice-covered Bárðarbunga caldera in central Iceland. Over the course of two weeks a dyke propagated 48 km beneath the glacier northeastwards and into the Holuhraun lava field, where it erupted for six months, becoming the largest eruption in Iceland for over 200 years. During this time, a gradual, incremental caldera collapse took place in the central volcano. The rifting episode was captured both geodetically and seismically. In this thesis, I analyse the seismic response to the event, both due to the dyke propagation, and the subsequent caldera collapse. This gives an insight into the underlying processes controlling rifting events, and the nature of the responding crust. The Cambridge seismic network recorded the 2014-15 Bárðarbunga-Holuhraun rifting episode in exceptional detail. I discuss the deployment and operation of this dense seismic network in the remote Icelandic highlands, as well as the campaign deployments on the volcano caldera, on the glacier (above the dyke path) and around the eventual eruption site, as a first response to the crisis. Using this dataset I have accurately located, and analysed, 47,000 earthquakes during the pre-intrusive, intrusive, eruptive and post-eruptive periods. Approximately 4,000 of the recorded earthquakes are associated with the caldera collapse, delineating faults accommodating the subsidence and showing good correlation with geodetic data. The seismicity reveals activation of both inner and outer caldera faults with 60 inward dipping planes on the northern and southern side, indicating a symmetric caldera structure. Detailed analysis of the earthquake source mechanisms shows that 90% can be explained by a double-couple solution, which is in contrast to results from previous studies of Bárðarbunga. I find the dominant failure mechanism during the collapse to be steep normal faulting, with sub-vertical P-axes, striking sub-parallel to the caldera rim. The northern and southern ...